Innovations in the olive oil sector: A fuzzy multicriteria approach. (15th August 2017) - Cappelletti, Giulio Mario; Grilli, Luca; Nicoletti, Giuseppe Martino; Russo, Carlo
Abstract: In recent years many technological innovations have been introduced into the olive oil sector, both into the farming system (high and super high density olive orchard) and into oil extraction techniques. As a result players in the sector have to consider different scenarios and have to evaluate many alternatives considering a number of economical, environmental and social criteria. In this paper we present a multicriteria approach in a fuzzy contest in which decision makers provide the assessment of alternatives and the evaluations of weights for criteria having recourse to linguistic variables. We consider a Triple Bottom Line model in a Multicriteria Fuzzy contest making use of the Triangular Fuzzy Theory in order to represent the decision makers' linguistic evaluations of criteria and alternatives. Starting from the decision makers' evaluations we compute the ranking of alternatives using the Fuzzy TOPSIS technique and we present a sensitivity analysis of the results. Results show that though there is no aggreement tor evaluate the best solution concerning cultivation systems, on the other hand, as to extraction processes, it is a common opinion to consider de-pitting as the best solution from an environmental, economic and social point of view. Anyhow, analisyng the final ranking, the combination of centuries-old olive orchard and de-pitting oil extraction is the best solution in absolute terms. This study highlights as innovations in olive oil sector, often developed only in an economic perspective, should be well investigated also in an environmental and social point of view. Despite the fact that it is not trivial to determine the best solution in absolute, sustainability should be taken in consideration in decision-making processes, especially in public policies both from a global and local point of view. Highlights: Olive oil production plays a very important role in the Mediterranean area. Cultivation systems and extraction techniques have changed in recent years involving economic, environmental and social implications. Multicriteria Analysis in a Fuzzy contest is applied to the different combinations of agricultural and industrial scenarios. Combination of the traditional cultivation system and innovative extraction system seems to be the optimal solution.